1991
DOI: 10.1007/bf00215075
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone perception in male pine sawflies, Neodiprion sertifer (Hymenoptera; Diprionidae)

Abstract: Electroantennographic and single sensillum recordings were performed on male pine sawfly, Neodiprion sertifer, antennae. Responses to the sex pheromone component (2S, 3S, 7S)- 3,7-dimethyl-2-pentadecenyl (diprionyl) acetate (SSS:OAc), to the behavioral inhibitor (2S, 3R, 7R)-diprionyl acetate (SRR:OAc), to the six other enantiomers of diprionyl acetate, and to the biosynthetic precursor diprionol were recorded. Responses to trans-perillenal, a monoterpene identified in female gland extracts and to (2S, 3S, 7S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…In Sweden none of the three analogs, (-SS)Ac, (S-S)Ac, or (SS-)Ac, elicited catches of males when used in traps by themselves, and, further did not did not affect the catches of males when added to (SSS)Ac. This suggests that the analogs did not bind effectively to the antennal receptors tuned to (SSS)Ac (Hansson et al, 1991). In Japan, however, (SS-)Ac, in amounts 10-20 times higher than that of (SSS)Ac, caught male N. sertifer in traps (tests 7 and 9, Tables 5 and 6).…”
Section: Baitmentioning
confidence: 84%
See 2 more Smart Citations
“…In Sweden none of the three analogs, (-SS)Ac, (S-S)Ac, or (SS-)Ac, elicited catches of males when used in traps by themselves, and, further did not did not affect the catches of males when added to (SSS)Ac. This suggests that the analogs did not bind effectively to the antennal receptors tuned to (SSS)Ac (Hansson et al, 1991). In Japan, however, (SS-)Ac, in amounts 10-20 times higher than that of (SSS)Ac, caught male N. sertifer in traps (tests 7 and 9, Tables 5 and 6).…”
Section: Baitmentioning
confidence: 84%
“…While the presence of a methyl group at each of the three stereogenic carbons apparently is essential to evoke an adequate response from males, the functional group on carbon 2 appears less critical; (SSS)Ac and (SSS)Pr are similarly active, both electrophysiologically and behaviorally (this study; Hansson et al, 1991;Anderbrant et al, 1992aAnderbrant et al, , 2000. Diprion pini shows an even broader tolerance to different esters, with the acetate, propionate, and iso-butyrate esters of (2S,3R,7R)-3,7-dimethyl-2-tridecanol being attractive Anderbrant et al, 2005).…”
Section: Baitmentioning
confidence: 91%
See 1 more Smart Citation
“…A blank solvent stimulus was included in all experiments to account for mechanical responses. The recorded EAG responses were normalized by using a standard stimulation (Hansson et al 1991) before (S b ) and after (S a ) each experimental stimulation (E). The responses were normalized according to E/ (S b + S a /2).…”
Section: Figmentioning
confidence: 99%
“…The European pine sawfly Neodiprion sertifer Geoffroy occurs in the northern hemisphere from Europe to eastern Asia and has been introduced into North America (Kolomiets et al, 1979). Adult females attract males with the aid of a sex pheromone (the acetate or propionate ester of (1S,2S,6S)-1,2,6-trimethyl-tetradecanol (diprionol)) and synthetic pheromone stimulates male antennae (Hansson et al, 1991) and attracts males in the field (Anderbrant et al, 1992b). It has been shown that N. sertifer males respond to synthetic pheromone from 200 m away (O È strand et al, 2000).…”
Section: Introductionmentioning
confidence: 99%